Bariery i możliwości rozwoju gospodarstw rolnych w opiniach ich właścicieli - Sulewski, Piotr (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2008)
In the paper farmers opinions about barriers and chances for farm’s development have been presented. The study was conducted on sample of 100 family farms. The main problem for a large majority of farms was low profitability of agricultural production. One third of the farmers indicated that they did not see any chance for development. The farmer’s opinions off their own farms were diversified depending on farms size and agricultural income